JUAN LARREA: LA UTOPIA MELANCOLICA (Res Publica. Revista de Historia de las Ideas Políticas, 2009)
This essay studies Larreaʼs proposal of an American utopia as the final synthesis of the opposites that surrealism had anticipated and the Spanish Republic had announced. Such a utopia, a compensation for the historical failure of the Spanish Republic, cannot hide its character as a melancholy response to loss.